The Genetic Status of the Critically Endangered Hainan Gibbon (Nomascus hainanus): A Species Moving Toward Extinction - Guo, Yanqing; Chang, Jiang; Han, Ling; Liu, Tao; Li, Gang; Garber, Paul A.; Xiao, Ning; Zhou, Jiang (Frontiers in Genetics, 2020)
The Hainan gibbon (Nomascus hainanus), once widespread across Hainan, China, is now found only in the Bawnagling National Nature Reserve. With a remaining population size of 33 individuals, it is the world’s rarest primate. Habitat loss and fragmentation are the primary drivers of Hainan gibbon population decline. In this study, we integrated data based on field investigations and genotype analyses of 10 microsatellite loci (from fecal samples) to assess genetic diversity in this Critically Endangered primate species. We found that the genetic diversity of the Hainan gibbon is extremely low, with 7 of 8 microsatellite loci exhibiting decreased diversity. Additional molecular analyses are consistent with field observations indicating that groups A, B, and C are closely related, the female-male sex ratio deviates significantly from 1:1, and the world’s remaining Hainan gibbon population is expected to experience continued high levels of inbreeding in the future. Given extensive habitat loss (99.9% of its natural range has been deforested) and fragmentation, this rarest of ape species faces impending extinction unless corrective measures are implemented immediately.